Fluid Field and Temperature Field Investigation of Traction Motor in Mine Truck - MENG Fandong; LI Huaxiang; JING Ruikang (Kongzhi Yu Xinxi Jishu)
According to hydromechanics and heat transfer theory, a physical model of three-dimensional fluid and temperature coupled field was established for JD192 electric wheel traction motor of mine truck. Considering the rotation of rotor effect, the fluid field and temperature field of the traction motor under the rated condition were calculated with finite volume method. Analysis of the numerical calculation results reveals the regularity of fluid flow and temperature distribution for the motor under high load condition, which verifies the effectiveness of the motor ventilation cooling structure and provides the basis subsequent improvement for the motor cooling.